2003
DOI: 10.1042/bj20030093
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone properties of Escherichia coli thioredoxin and thioredoxin reductase

Abstract: Thioredoxin, thioredoxin reductase and NADPH form the thioredoxin system and are the major cellular protein disulphide reductase. We report here that Escherichia coli thioredoxin and thioredoxin reductase interact with unfolded and denatured proteins, in a manner similar to that of molecular chaperones that are involved in protein folding and protein renaturation after stress. Thioredoxin and/or thioredoxin reductase promote the functional folding of citrate synthase and alpha-glucosidase after urea denaturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 45 publications
2
101
1
1
Order By: Relevance
“…Mitochondria may play a dominant role in aging process and development in worms, and mitochondrial TrxR may contribute to protect mitochondria from the oxidative damage. In those regards, it has been shown that the deficiency of mitochondrial redox enzymes results in the increased sensitivity to the oxidative stress and mitochondrial defects in C. elegans (Kern et al, 2003). Interestingly, the depletion of trxr-2, but not trx-2 has been reported to aggravate aging-dependent paralysis caused by the muscle-specific expression of human β-amyloid, which forms pathological plaque aggregates in the brain of Alzheimer's disease patients where the oxidative stress is a prominent factor of the disease etiology (Barstead, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria may play a dominant role in aging process and development in worms, and mitochondrial TrxR may contribute to protect mitochondria from the oxidative damage. In those regards, it has been shown that the deficiency of mitochondrial redox enzymes results in the increased sensitivity to the oxidative stress and mitochondrial defects in C. elegans (Kern et al, 2003). Interestingly, the depletion of trxr-2, but not trx-2 has been reported to aggravate aging-dependent paralysis caused by the muscle-specific expression of human β-amyloid, which forms pathological plaque aggregates in the brain of Alzheimer's disease patients where the oxidative stress is a prominent factor of the disease etiology (Barstead, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…Immature conformers of OmpA fold in the periplasm (43). Thioredoxin has a chaperone activity (44), and the colocalization of thioredoxin could be indicative of a role in protein folding in the periplasm. This association may also indicate a role for thioredoxin as a receptor for bacteriophages.…”
Section: Thioredoxin-associated Pathwaysmentioning
confidence: 99%
“…Given that the E. coli Trx (19) and PDI (20), which contain a Trx motif and 2 Cys Prxs (14) with a Trx fold, exhibit chaperone functions, we explored the functions of AtTDX from Arabidopsis in the present study. We demonstrated in a plant system that an Arabidopsis Trx-like protein, AtTDX, displayed multiple functions that depended on its oligomeric status, alternatively acting as a disulfide reductase, foldase chaperone, and holdase chaperone.…”
mentioning
confidence: 99%
“…1D). In addition, given that E. coli Trx exhibits a foldase chaperone function (19), we also examined the foldase chaperone activity of AtTDX by using glucose-6-phosphate dehydrogenase (G6PDH). To distinguish the foldase chaperone function of AtTDX from its disulfide reductase function, the Cys-free form of G6PDH was used (21).…”
mentioning
confidence: 99%